Association between urinary glyphosate levels and hand grip strength in a representative sample of US adults: NHANES 2013–2014 - Fang, Yu-Wei; Wang, ChiKang; Lin, Chien-Yu (Frontiers in Public Health, 2024)
Glyphosate, a widely utilized herbicide globally, has been linked to various health issues, including cancer, birth abnormalities, and reproductive issues. Additionally, there is growing experimental support indicating potential harm to skeletal muscles. Despite this, the impact of glyphosate on human muscle health remains unclear. We examined information gathered from the 2013-2014 National Health and Nutrition Examination Survey (NHANES), which included 1466 adults aged 18 or older. Our primary aim was to investigate the relationship between glyphosate exposure and hand grip strength, as well as its influence on lean muscle mass. Our investigation uncovered a detrimental correlation between glyphosate exposure and all measures of grip strength, except for the second test of the first hand. Specifically, we observed a statistically significant adverse association between glyphosate exposure and combined grip strength, which is calculated as the sum of the highest readings from both hands (ß coefficient of -2.000, S.E. = 0.891, P = 0.040). We did not observe a significant correlation between glyphosate levels, lean muscle mass, and the likelihood of reaching maximum grip strength meeting sarcopenia criteria. Additionally, we observed an interaction between age and glyphosate, as well as between body mass index (BMI) and glyphosate, concerning the association with combined grip strength. In this comprehensive analysis of NHANES data, our study reveals a potential association between glyphosate exposure and hand grip strength in the adult population. Our findings suggest the need for deeper exploration into the health effects of glyphosate exposure and its impact on muscle strength, shedding light on possible public health concerns.